Property Taxation in Relation to Investment in Urban Areas: Discussion - Ford, Robert S. (Journal of Finance, 1951)
A FEW POINTS of a footnote character are about all that I can add to Dr. Mitchell's paper.The imposition of any tax will affect, to some extent, the pattern of consumption, saving, and investment and thus exercise some influence on the allocation of resources.Certain taxes, of course, will have less effect than others and this appears to be the case with the property tax, except for investment in urban rental housing.While there are significant variations in effective rates on different types of property and property in different locations, the factor of deductibility of property tax in computing income tax tends to minimize somewhat the effect of differentials between effective tax rates in different localities; Thus, this factor would simply contribute to the neutral effect of property tax on investment.For manufacturing industry, the tax appears to have exercised little, if any, influence on the incentive to expand plant and equipment.Dr. Mitchell points out that investment in residential rental housing and rental office loft space is probably the most sensitive to prop-